Scaffold-free, stem cell-based cartilage repair - Yasui, Yukihiko (J Clin Orthop Trauma, 2016)
Various approaches to treat articular cartilage have been widely investigated due to its poor intrinsic healing capacity. Stem cell-based therapy could be a promising approach as an alternative to chondrocyte-based therapy and some of these therapies have been already applied in clinical condition. This review discusses the current development of stem cell-based therapies in cartilage repair, specifically focusing on scaffold-free approaches.